Intrapersonal and interpersonal level factors influencing self-care practices among Hong Kong individuals with COVID-19—A qualitative study - Ma, Haixia; Ma, Yajing; Ge, Song; Wang, Shanshan; Zhao, Ivy Yan; Christensen, Martin (Frontiers in Public Health, 2022)
Background The unprecedented crisis during the fifth wave of the COVID-19 pandemic in Hong Kong placed a significant burden on the health care system. Therefore, the Hong Kong government advocated that individuals with no or mild COVID-19 symptoms should self-care at home. This study aimed to understand intrapersonal and interpersonal level factors that shaped self-care practices among home-quarantined individuals with COVID-19 during the peak of the pandemic. Methods This study used convenience and snowball sampling whereby a total of 30 semi-structured telephone interviews were conducted between March and April 2022. Inductive content analysis was used to analyze the data. Results Factors reported at the intrapersonal level included socioeconomic status and housing conditions, information and knowledge about COVID-19, long COVID, and psychological adjustments brought about by home quarantine. Factors identified at the interpersonal level included caregiving responsibilities, family relationships, and social support. Conclusions Findings from this study identified a combination of intra and interpersonal level factors influenced an individual's self-care practices as a result of pandemic-induced quarantine. It was particularly concerning for those individuals in socially and economically deprived groups, where access to services was challenging. This study also raised awareness of the ineffectual and insufficient knowledge individuals held of self-medication and overall COVID-19 management. A key recommendation is developing family-based resilience programmes to support and empower vulnerable families to better cope with the realities of self-quarantine.